凍結加温手術装置における温度サイクル性能の評価 - 相田, 武則; 田口, 洋介; 高橋, 大志 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
The combination treatment system of cryosurgery and hyperthermia treatment was fabricated. This system consists of a surgical probe utilizing Peltier device, the power with temperature control function, Stirling cooler attaching the coolant chamber and a peristaltic pump for circulating liquid ethanol as a coolant. In the fabrication of the system, Peltier device was attached to a hand-piece. The coolant chamber was fixed to Stirling cooler using a thermal conductive adhesive bond. The surgical probe and the coolant chamber was connected with the tube for peristaltic pump, thus the combination system was fabricated. In the evaluation of the system performances, the temperature of the probe reached to -53 degrees C and three temperature cycles of the freezing and the warming could be performed. The result suggests the feasibility of the combination treatment. This work was partly supported by JSPS Grants-in-Aid for Young Scientists (B) number 26820065.